Diagnostic Accuracy of Gastroscopy with Narrow Band Imaging for the Diagnosis of Helicobacter Pylori Gastritis : Gastroscopy for the Diagnosis of Helicobacter Pylori Gastritis - Rehan, Bushra; Ul-Haq, Muhammad Mansoor; Kumar, Rajesha; Akmal, Mehreen (Pakistan Journal of Health Sciences, 2024)
Helicobacter pylori infection promotes stomach cancer and chronic gastritis globally. Endoscopic features that may identify H. pylori are being explored. Objective: Narrow Band Imaging (NBI) is used to identify and treat H. pylori gastritis before biopsy since most patients are lost to follow-up or follow-up is too late. H. pylori gastritis may be treated early to improve quality of life and gastrointestinal concerns. Methods: This cross-sectional study at Department of Gastroenterology, Liaquat National Hospital, Karachi, conducted between 1st March 2022 till 28th February 2023, included 150 patients. Patients with gastritis on endoscopy were evaluated for the presence of H. pylori with Narrow band Imagining. Findings were compared with histopathology as gold standard. Results: Mean age of the patients was 41.87 ± 12.5 years. Male participants were 71 (47.3%). The most common admission complaints were nausea, appetite loss, and abdominal distension. The diagnostic accuracy of NBI for the detection of H. pylori was 85% sensitivity, 88% specificity, 88% positive predictive value, 87% negative predictive value and overall accuracy of 88%. NBI endoscopy was cheaper and took less time to diagnose (27 minutes vs. 37 minutes). NBI endoscopy is more effective and cost-effective than standard gastroscopy. Conclusions: The data confirm the high incidence of H. pylori in gastrointestinal patients. NBI endoscopy is more effective and cost-effective than standard gastroscopy.